2016
DOI: 10.1007/s11695-016-2070-y
|View full text |Cite
|
Sign up to set email alerts
|

Severe Vitamin D Deficiency Is Not Associated with Liver Damage in Morbidly Obese Patients

Abstract: Low levels of 25-OH vitamin D were not independently associated with liver damage in morbidly obese patients with non-alcoholic fatty liver diseases (NAFLD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…In addition, when we search through the previous studies, the data are rather limited for generalizability because most of the studies involved small number of patients [ 5 , 13 ] or a specific population that already has risk factors for NAFLD, e.g., diabetes or obesity [ 13 ]. Therefore, we attempted to elucidate the association between vitamin D insufficiency and NAFLD in a large number of nationally representative samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, when we search through the previous studies, the data are rather limited for generalizability because most of the studies involved small number of patients [ 5 , 13 ] or a specific population that already has risk factors for NAFLD, e.g., diabetes or obesity [ 13 ]. Therefore, we attempted to elucidate the association between vitamin D insufficiency and NAFLD in a large number of nationally representative samples.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, regarding nonalcoholic fatty liver disease (NAFLD) among chronic liver diseases, previous studies have largely reported that vitamin D insufficiency was associated with the presence [ 6 , 7 , 8 , 9 ] or severity [ 10 , 11 ] of NAFLD. However, some other studies reported quite contradictory results [ 12 , 13 ], and one experimental study even argued that vitamin D insufficiency alleviated accumulation of liver fat [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…12,[69][70][71] Although low vitamin D levels are significantly associated with NAFLD severity in both Asian and Western studies, the therapeutic role of vitamin D supplementation is unclear. 72 Likewise, the effect of hypothyroidism on NAFLD is unclear. 73,74 Non-obese NAFLD While NAFLD is strongly associated with obesity and metabolic syndrome, a proportion of NAFLD patients have relatively normal BMI.…”
Section: Othersmentioning
confidence: 99%
“…We also conducted a meta-regression to determine whether there was an association between serum vitamin D levels and METAVIR stage of liver fibrosis (F0-F4) in NAFLD. As shown in Table 4 , there are conflicting reports with three studies demonstrating significance ( P < 0.05)[ 26 , 27 , 32 ] and three finding no association ( P > 0.05)[ 28 - 30 ]. Our meta-regression did not find an association between vitamin D level and fibrosis stage across the studies.…”
Section: Discussionmentioning
confidence: 99%